Yield and physiological response of potatoes indicate different strategies to cope with drought stress and nitrogen fertilization - Saravia, D.; Farfán Vignolo, E.; Gutiérrez, R.; Mendiburu, F. de; Schafleitner, R.; Bonierbale, Merideth W.; Khan, M.A. (Springer, 2016)
Access to Water and Nitrogen (N) are key challenges in potato crop management that could be optimized through understanding related agronomic and physiological traits. The responses to water deficit and two levels of nitrogen (0 and 200 kg N.ha-1) were assessed here for agronomic and physiological traits for potato genotypes UNICA, Achirana-INTA, and CIP397077.16, chosen for their short vegetative period (90–-110 days) and tolerance to water deficit. Nitrogen Use Efficiency (NUE) was greatly reduced in all genotypes under drought, even dropping to nearly zero. Despite this, the tuber yield and total biomass reduction of around 50 % for all genotypes could be alleviated with N application. Normalized Difference Vegetation Index (NDVI), chlorophyll content (SPAD), and Canopy cover (CC) were found to be good indicators for predicting nitrogen deficits and detecting early stress by drought. Overall, each genotype had different strategies to manage N and cope with drought stress. UNICA was the most efficient genotype at using the N present in the soil and tolerating drought stress, while Achirana-INTA was most affected by drought in terms of NUE. Based on the results, it is suggested that maximum fertilizer use efficiency can be obtained with low N rates applied under well-watered conditions. Improved NUE and a greater understanding of the physiological response of crops to drought stress and N fertilization will help to reduce fertilizer use, lessening the effects of water contamination and improving input efficiency.